Health Benefits Of Pectin: A Review Of Scientific Evidence And Consumption Dosage Recommendations - Sri Puji Rahayu (JURNAL KESMAS DAN GIZI (JKG), 2025)
Pectin is a soluble dietary fiber component commonly found in plant cell walls and has garnered significant attention in the field of functional foods due to its diverse health benefits. This article aims to systematically review scientific evidence regarding the health benefits of pectin and its recommended consumption dosage. The method used is a literature review by collecting articles from various scientific databases such as Google Scholar and PubMed within the range of 2014–2024. The review findings indicate that pectin has positive effects in lowering LDL cholesterol, triglycerides, and blood glucose levels. Additionally, pectin shows potential as an anti-cancer agent through the inhibition of Galectin-3, as well as demonstrating immunomodulatory activity and a key role in maintaining gut health. Pectin has also been shown to be safe as a biomaterial based on cytotoxicity tests on human cell cultures. The recommended dosage of pectin varies depending on its intended use, with an effective range in humans between 15–30 grams per day. However, excessive intake may cause mild digestive discomfort such as bloating or gas; therefore, gradual consumption is advised. In conclusion, pectin holds great potential as a functional food component and therapeutic agent. Nevertheless, further research is needed to evaluate its effectiveness in human populations, determine optimal dosage, and explore its interactions with other dietary components. In addition, the development of high-bioavailability pectin-based products could be a strategic approach to maximizing its health benefits.